The role of consumption orientation in consumer food preferences in emerging markets - Salnikova, Ekaterina; Grunert, Klaus G. (Elsevier, 2020)
Global marketers are widely implementing global or local product positioning in an attempt to appeal to consumers in international markets. However, there is no consensus in homogenization versus heterogenization of consumer needs and globalization vs. localization of the marketplace. This paper examines the relationship between consumption orientation and the use of various extrinsic and intrinsic product attributes by consumers in emerging markets. This paper employs a discrete choice experiment to explore the preferences of consumers with glocal, local, and global orientations from six emerging markets using fresh pork as a stimulus. We found that consumer orientation impacts consumer preferences for pork products. Product origin was the most important attribute in the evaluation of products across all countries. Local consumers placed higher importance on origin than glocal and global consumers. Glocal consumers were found to be the biggest segment with their own unique blend of preference for products with various attributes.
Keywords: consumption orientation; consumer culture; extrinsic and intrinsic product attributes; country of origin; choice experiment; emerging markets; consumers; consumer behaviour; consumption; foodstuffs; emerging markets; consumer habits; marketing; international market; international marketing; internal marketing; fi=Markkinointi|en=Marketing|